Pelatihan Membangun Website Desa Dan Sistem Informasi Di Desa Sragi Kabupaten Ponorogo - Arohma Putri Kaharidoni; Ajeng Wahyuni (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Currently, technology is developing increasingly sophisticated, making it easier for users who are marked by the use of the internet which can convey, disseminate, and obtain information easily. The information provided is also diverse, there are aspects of education, business, news, entertainment, and much more. Sragi Village is a village located in the middle of the city, precisely in Sukorejo District, Ponorogo Regency. The problem that arises and is faced is that not many people know this village and the lack of skills of village officials in the conventional management system. To make it easier to process village archives, the conventional management system must be changed to digital by creating or building a village website which will later be used to publish the potential and all assets owned so that the wider community can find out information about Sragi village and get to know the Sragi village better. In addition, this can make village officials skills in managing village archives using a digital system. Villagers can also disseminate information about the business they run so that many are aware of and may be able to get consumers from inside and outside the village. This is an advantage for the village of Sragi itself which is increasingly being known by the wider community.